The book of ruth eaudiobook - Hamilton, Jane (Recorded Books, 1997)
Winner of the 1989 PEN/Hemingway Foundation Award for best first novel, this exquisite book confronts real-life issues of alienation and violence from which the author creates a stunning testament to the human capacity for mercy, compassion and love. "An American beauty this book. ... The narrator of Jane Hamilton's sensational first novel is a holy lusty innocent."—Vogue